Impact of Agroecological Practices on Agricultural Production in the Kirimiro Plateaux of Burundi (London Journal of Research In Science: Natural and Formal, 2025)
This study was conducted to analyze the impact of agroecological practices on agricultural production, focusing on the main crops and their determinants in central Burundi. A three-stage sampling method was used to collect primary data from 252 farming households, including 125 that implemented agroecological practices and 127 control households. The results indicate that factors such as years of experience in agroecology, use of biofertilizers, agricultural training, access to credit, and seed category influence maize production in the region. The average maize production per hectare is 1903.01 kg/ha for the group that adopted agroecological practices compared to 1027.46 kg/ha for the control group during the 2023-2024 growing season.
Keywords: Discrete maximum principle; geometric arguments; diffusion-advection-reaction problems; finite volume schemes; agroecological practices; agricultural production; Kirimiro; Burundi